STUDI MINERALISASI DAN ALTERASI DAERAH KESI DAN SEKITARNYA, SUMBAWA, NUSA TENGGARA BARAT - Elsandy Purnomo, Luvian
The research area is located in Kesi area and its surroundings, Sumbawa Regency, Nusa Tenggara Barat Province. Geographically, the study area is located at the coordinates of UTM 542200-543600 mT and 9010500-9014400 mU zone of 50S based on datum WGS 1984 covers 5.46 km2 area (3,9 km x 1,4 km). This research aims to determine the geological conditions of the study area including geomorphological, lithology distribution, and structural geology, distribution of alteration and mineralization, their paragenesis, and the relationship of alteration-mineralization. Field data were collected from the mapping on scale of 1: 5000, while the method applied in this research were geological structure analysis, petrographic analysis, and mineragraphic analysis. The research area consists of hills and valley, its altitude range from 350 to 650 meters above sea level with slightly steep to steep slope, the lineament oriented north-south to northeastsouthwest, while the geomorphic state is old. The lithology of the study area classified into four non formal units, there are volcanic, quartz diorite, and microdiorite of Middle Miocene-Late Miocene in age, and Kuarter-aged of alluvial deposits. The structural geology divided into primary structure as bedding and secondary structure as sinistral fault, fractures, vein, intrusion contact, and clay-dyke at the northeast-southwest corridor. Alteration of the study area is divided into four zones, there are early quartz + epidote + actinolite ± garnet ± secondary biotite at the central and chlorite + epidote at the proximal, while the latter stage chlorite + sericite ± quartz ± clay minerals and sericite + quartz + clay minerals. Mineralization develops in the form of magnetite, bornite, chalcopyrite, pyrite, covellites, chalcocite, hematite and malachite. Geological process start with development of volcanic rock at Middle Miocene, then comes quartz diorite intrusion accompanied by the presence of northeast-southwest corridor structures. After that early alteration and mineralization develop. Microdiorite comes intrude quartz diorite while tle later stage of alteration and mineralization occur and overprint the previous ones.